Cu, Zn doped borate bioactive glasses: antibacterial efficacy and dose-dependent in vitro modulation of murine dendritic cells - Schuhladen, Katharina; Stich, Lena; Schmidt, Jochen; Steinkasserer, Alexander; Boccaccini, Aldo R.; Zinser, Elisabeth (Biomaterials Science, 2020)
Among emerging biomaterials, bioactive glasses (BGs) are being widely explored for various applications in tissue engineering. However, the effects of BGs (in particular BG ionic dissolution products) on immune cells and specifically on dendritic cells (DCs), which are the most potent antigen-presenting cells of the immune system, have not been previously investigated in detail. Such interactions between BGs and DCs must be assessed as a novel biocompatibility criterion for biomaterials, since, with the increased application possibilities of BGs, the modulation of the immune system may induce potential complications and undesired side effects. Indeed, the effects of BG exposure on specific immune cells are not well understood. Thus, in this study we investigated, for the first time, the effect of borate BGs doped with biologically active ions on specific immune cells, such as DCs and we further investigated the antibacterial properties of these borate BGs. The compositions of the borate BGs (B3) were based on the well-known 13-93 (silicate) composition by replacing silica with boron trioxide and by adding copper (3 wt%) and/or zinc (1 wt%). By performing an agar diffusion test, the antibacterial effect depending on the compositions of the borate BGs could be proved. Furthermore we found a dose-dependent immune modulation of DCs after treatment with borate BGs, especially when the borate BGs contained Zn and/or Cu. Depending on the ion concentration and the rise in pH, the phenotype and function of DCs were modified. While at low doses B3 and Zn-doped B3 BGs had no impact on DC viability, Cu containing BGs strongly affected cell viability. Furthermore, the surface expression of DC-specific activation markers, such as the major histocompatibility complex (MHC)-II, CD86 and CD80, was modulated. In addition, also DC mediated T-cell proliferation was remarkably reduced when treated with high doses of B3-Cu and B3-Cu-Zn BGs. Interestingly, the release of inflammatory cytokines increased after incubation with B3 and B3-Zn BGs compared to mock-treated DCs. Considering the essential role of DCs in the modulation and regulation of immune responses, these findings provide first evidence of phenotypic and functional consequences regarding the exposure of DCs to BGs in vitro.
CRIS-Team Scopus Importer:2020-04-28